Pengaruh Komunikasi Massa Instagram MedanTalk Terhadap Pemenuhan Kebutuhan Informasi Warga Kota Medan - Wahyudi, Arif; Hidayat, Taufik Wal; Riadi, Selamat (Universitas Medan Area, 2025)
This study was conducted on followers of the MedanTalk Instagram account with the aim of analyzing the influence of mass communication on fulfilling the information needs of Medan City residents. The background of this research lies in the increasing reliance of urban communities on social media as an alternative source of fast, accessible, and interactive information. The study population consisted of 1.8 million MedanTalk followers, with a sample of 100 respondents selected through purposive sampling to ensure alignment with the research objectives. Data were collected through online questionnaires and analyzed using simple linear regression to examine the relationship between mass communication and the fulfillment of information needs. The findings indicate that mass communication through the MedanTalk account has a positive and significant effect on meeting the information needs of Medan residents, with a regression coefficient value of 0.957. This suggests that the more intensive the use of mass communication via social media, the greater the extent to which public information needs are fulfilled. These results are consistent with the Uses and Gratification Theory, which emphasizes that audiences actively engage with media to satisfy cognitive, social, functional, and entertainment needs. This research contributes significantly to the development of digital communication studies, highlighting that local social media platforms such as MedanTalk play a strategic role in providing relevant, timely, and credible information to the public in the digital era.